A Study on the Production and Operations Management System of Tact Imaging and Supplies, Incorporated - De Leon, Ma. Cecilia (College of Engineering, 1999)
A documentation of the production and operations management system of TACT Imaging and Supplies was conducted. TACT is an ISO 9002 certified company that produces computer printer ink ribbons for both local market and export. The problems observed during documentation were evaluated using Streamline Analysis, and further analyzed using Cause and Effect Diagrams. Three major problems of the company were noted: (1) improper procedure for job assignment, (2) forecast does not reflect actual demand, and, (3) stockouts or excess inventory. The company presently uses the 12-mopnth simple moving average to forecast demand. Historical and forecast demand data for 1998 reveal that the current method does not yield accurate results. Other techniques were evaluated, by obtaining forecasts for 1998, and comparing with the actual values. The simple exponential smoothing with a=0.8 gave the best results. In addition, the exponential smoothing method is relatively easy to compute and requires less historical data. TACT bases its order quantity on its demand forecasts, which was shown to be beyond acceptable limits. Forecasts that are less than actual demand cause the occurrence of stockouts while those that are less than actual demand lead to excess inventory. The inclusions of the safety stock, specified as a percentage of the demand forecast were evaluated. A time study of the processes in the production of computer printer cartridges was conducted. This would provide management with a benchmark for worker performance, and thus serve as a basis for job assignment. Standard times also allow for proper job scheduling, so the company could increase the capacity utilization rate of their production lines.